Kelekatan Orang Tua dan Kecemasan Sosial sebagai Faktor Penentu Kesepian Remaja Pengguna Media Sosial - Berlianza, Amelia; Pramono, Ridwan Budi (Universitas Syiah Kuala, 2025)
Teenagers' usage of social media is frequently associated with emotional instability, especially loneliness. This study investigates the connection between social anxiety and loneliness in adolescents who use social media often and parental attachment. Participants in the study, who ranged in age from 13 to 21, were recruited using a correlational quantitative methodology. Purposive sampling was used to choose a total of 100 responders. Three Likert-based psychological measures evaluating social anxiety, parental attachment, and loneliness were used to gather data. The validity and reliability of every instrument were examined. Multiple regression and Pearson correlation were performed once the normality and linearity tests were completed. The findings indicated a strong positive correlation between loneliness and social anxiety. In contrast to the hypothesis, a significant positive relationship was also found between parental attachment and loneliness, suggesting that a strong emotional bond with parents does not always reduce loneliness. Adolescents may still experience emotional distress due to insecure attachment styles, such as anxious attachment. This study concludes that both parental attachment and social anxiety contribute to adolescent loneliness, especially in the context of frequent social media use.